Letter from Carl D. Duncan to Patricia Whiting, September 1, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan explains how Patricia Whiting and her family have fulfilled his sense of purpose that he almost lost after his wife Neva passed away.